Izzivi sodobnega slovenskega slovaropisja (University of Maribor Press, 2011)
Challenges of contemporary Slovene Glossary Writhing. Pišak is inscribed on the basic topographic plan as the name of the hill near Pišec (TTN5), and, according to the locals, Pišák is the name of a larger area 2 km south of the center of Pišec, a hilly ridge where vineyards used to be. Since the local dialect is characterized by the assimilation of sch> š, e.g. writes for ’piss’, stitches for ’stitches’ (for information on the hermit name and local speech I thank Mrs Marjanci Ogorevc and Mr Martin Dušic), it is obvious that Pišak is the original * Pišcak. The base of this name is probably the same as in the verb spelled in Bela krajina in the sense of ’cure’, or in hrv. whistle and whistle to squirt, all from psl. * pee in the same sense. Even the appellate cookie in the sense of ’spring’ is preserved in the chakra (M. Furlan v Bezlaj 1995: 42, s.v. pee). This is also motivated by the fact that the nearby village of Vitna has the village of Pišak, where there are three stronger springs (KLS 1976: 48). The local name Pišece was probably derived from the conversion from the town form of water and glacial name * Pišcak, namely (v) * Pišcace, similar to Jesenice (<* asenik), Lesce (<* luster or * luster), Žahenberc (<Žahenberk). The Slovene population eventually adopted the German-proclaimed form of Pisca instead of the domestic Pisca (regarding the influence of the German pronunciation, cf. Tacen <* Tesno, Torkar 2006: 173), especially since it is aquatic and glacial. the local name was taken over by the German feudal lord for the name of the castle, thus greatly increasing the frequency of use of the name.